Biodiversidade subterrânea em cavernas da Guatemala: influências do habitat físico e impactos causados pela atividade turística - Pacheco, Gabrielle Soares Muniz (2019)
This dissertation is developed on subjects related to the ecology of subterranean natural cavities, more specifically on the influence of substrate and tourism activity on the species composition and richness of terrestrial invertebrate fauna in caves. For this work, terrestrial invertebrates were collected in ten cavities in the karst regions of Alta Verapaz and Petén, Guatemala, between June and July of 2017. It contains two scientific papers, written in scientific journal format. The first was written according to the norms of the “International Journal of Speleology” journal. The objective of this chapter was to investigate the similarities of the cave invertebrate fauna from the ten caves included in this study and to investigate which substrate features have the greatest influence on the structure of the cave invertebrate community in Guatemala. The second chapter was elaborated according to the norms of the “Tourism Management” journal and had the objective of measuring possible effects of tourism on the community of terrestrial invertebrates in Gruta de Lanquín, Lanquín municipality, Alta Verapaz region, Guatemala. Thus, contributing to the knowledge, management and conservation of the biospeleological patrimony of the Guatemala.